Clinical factors affecting costs in patients receiving systemic antifungal therapy in intensive care units in Greece: Results from the ESTIMATOR study. Issue 7 (20th April 2017) - Armaganidis, A.; Nanas, S.; Antoniadou, E.; Mandragos, K.; Liakou, K.; Koutsoukou, A.; Baltopoulos, G.; Nakos, G.; Kounougeri, A.; Ganas, K.; Prekates, A.; Kompoti, M.; et al.
Summary: Invasive fungal infections are common in intensive care units (ICUs) but there is a great variability in factors affecting costs of different antifungal treatment strategies in clinical practice. To determine factors affecting treatment cost in adult ICU patients with or without documented invasive fungal infection receiving systemic antifungal therapy (SAT) we have performed a prospective, multicentre, observational study enrolling patients receiving SAT in participating ICUs in Greece. During the study period, 155 patients received SAT at 14 participating ICUs: 37 (23.9%) for proven fungal infection before treatment began, 10 (6.5%) prophylactically, 77 (49.7%) empirically and 31 (20.0%) pre‐emptively; 66 patients receiving early SAT (55.9%) were subsequently confirmed to have proven infection with Candida spp. (eight while on treatment). The most frequently used antifungal drugs were echinocandins (89/155; 57.4%), fluconazole (31/155; 20%) and itraconazole (20/155; 12.9%). Mean total cost per patient by SAT strategy was €20 458 (proven), €15 054 (prophylaxis), €23 594 (empiric) and €22 184 (pre‐emptive). Factors associated with significantly increased cost were initial treatment failure, length of stay (LOS) in ICU before starting SAT (i.e. from admission until treatment start), fever and proven candidaemia (all P ≤.05). Conclusion: Early administration of antifungal drugs was not a substantial component of total hospital costs. However, there was a significant adverse impact on costs with increasing LOS in febrile patients in ICU for whom diagnosis of fungaemia was delayed before starting SAT, and with initial treatment failure. Awareness of potential candidaemia and initiation of pre‐emptive or empirical strategy as early appropriate treatment may improve ICU patient outcomes while reducing direct medical costs.